Eyes Gone To Seed - Andersen, Katie (Pivot: A Journal of Interdisciplinary Studies and Thought, 2023)
Endometriosis and adenomyosis are chronic diseases which affect 1/10 people with uteruses and are drastically understudied and underserved in the Canadian healthcare system. Through experimentation with blank space on the page, this poem explores some aspects of what it means and how it feels to live with and seek treatment for these diseases.